HIV‐1 subtype frequency in Northeast Brazil: A systematic review and meta‐analysis. Issue 12 (28th April 2020) - da Costa, Clevson P.; Rodrigues, Jessyca K. F.; de Morais, Viviane M. S.; de Andrade, Carlos A. d. N.; Neves, Patrícia A. F.; Lima, Kledoaldo
Abstract: Information on human immunodeficiency virus (HIV) molecular epidemiology is required to verify HIV/AIDS (acquired immune deficiency syndrome) epidemic dynamics in different regions, as well as provide support for response to antiretroviral therapy, transmission of resistance mutations, disease progression, and viral spread. The aim of this study was to conduct a systematic review and meta‐analysis of the frequency of HIV‐1 subtypes in Northeast Brazil. Seventy‐six articles that refer to HIV‐1 and its subtypes in the Northeast Brazil and published between 1 January 1999 and 31 August 2019 were identified. We included 27 articles for the qualitative synthesis, thus analyzing results from 4466 patients and 4298 genomic sequences. The results showed that subtypes B, F, and C and recombinant BF were responsible for 76% (IC95%: 71‐80), 8% (IC95%: 5‐11), 2% (IC95%: 2‐3), and 7% (IC95%: 4‐12) infections, respectively. The highest proportion of subtype B infections (82.2%) was observed in Piauí, while the subtype F had a high frequency in Pernambuco (23.4%). Bahia presented 11.6% of the proportion of recombinant BF. In addition, several recombinants such as AG, BC, BCF, and BD have been identified in the region. This is the first systematic review and meta‐analysis on the HIV‐1 subtype distribution in Northeast Brazil and has shown a high circulating viral diversity. Although subtype B is predominant in Brazil, a large frequency of non‐B subtypes has also been found, which may have consequences for response to antiretroviral therapy, disease progression, and transmission. Thus, HIV molecular epidemiological data are essential for epidemic prevention and control strategies. Research Highlights: A large number of studies were analyzed for only one region of a country (n = 27), with a total of 4298 HIV‐1 sequences. The Northeast region of Brazil, the second most populous in the country, has a variety of HIV‐1 subtypes and Circulating Recombinants Forms. There is a predominance of subtype B. However, in some states there are high proportions of other subtypes and recombinants.